Answer:
The value of b for the equation to have no solution is;
![b=(1)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/p5bwm5wj83p27npjr489vw69qum7h9a02y.png)
Step-by-step explanation:
Given the the equation;
![(4b+2)x-7=10bx-12](https://img.qammunity.org/2023/formulas/mathematics/college/e8h3yq51981c6aa2uh2i8b9o6ix0v12ok2.png)
solving we have;
![\begin{gathered} 4bx+2x-7=10bx-12 \\ 2x+4bx-10bx=-12+7 \\ 2x-6bx=-5 \\ x(2-6b)=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7j7nf934tg32bovzggvnkq5kg6maanehru.png)
for x to have a solution, the product of x and (2-6b) must not be equal to zero.
So, the value of b for the equation to have no solution can be derived by equating (2-6b) to zero;
![\begin{gathered} (2-6b)=0 \\ 2=6b\text{ -----add 6b to both sides} \\ b=(2)/(6)\text{ ------divide both sides by 6} \\ b=(1)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4edcv9eitt3mgr79p7dolqpclt0b41p9qb.png)
Therefore, the value of b for the equation to have no solution is;
![b=(1)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/p5bwm5wj83p27npjr489vw69qum7h9a02y.png)